Amplification of gravitational motion via quantum weak measurement. (28th April 2019) - Kawana, Kiyoharu; Ueda, Daiki
Abstract: We investigate a new experimental possibility of measuring the Newtonian gravitational constant G by using weak measurement. Amplification via weak measurement is an interesting phenomenon of quantum mechanics. In this letter, we consider it in a system consisting of many cold atoms that are gravitationally interacting with an external macroscopic source and show that it is possible to obtain O(10^3) amplification of their relative motion compared with the classical motion when the number of atoms is O(10^15) and the observing time is 0.5 s. This result suggests that it might be possible to use this system as a new experimental setup for determining G . In addition, our study indicates that the gravitational force can behave as a repulsive force because of the weak measurement.